Can Expenditure Cuts Eliminate a Budget Deficit?: The Australian Experience - George Argyrous (Levy Economics Institute of Bard College, 1998)
Australian governments since the late 1970s have attempted to eliminate the fiscal deficit through reductions in expenditure. These efforts have failed. With each successive business cycle the federal government's budget outcome has been an ever-growing deficit. This paper explains the failure of the government to achieve its balanced budget objective through expenditure reductions. It argues that the impact of these expenditure reductions on the course of the business cycle and the long-term development of the economy has actually fed back onto the budget outcome in a negative way. These feedbacks have rendered the instruments for achieving the government's objective self-defeating. The paper explores the compositional changes in government outlays, away from capital to current outlays, that have resulted from this policy and which may have a detrimental effect on long-run growth.
Keywords: 330